CA19-9-Producing early gastric adenocarcinoma arising in hyperplastic foveolar polyp: a very unique resection case - Guo Xin; Yamada Sohsuke; Omori Haruki; Wang Ke-Yong; Tasaki Takashi; Nabeshima Atsunori; Kohno Kimitoshi; Sasaguri Yasuyuki (Diagnostic Pathology, 2011)
Abstract Here we report the first case of carbohydrate antigen (CA) 19-9-producing early gastric adenocarcinoma arising in polyp. A solitary pedunculated polyp lesion of the stomach, measuring 26 × 20 × 20 mm, was noticed in a 76-year-old Japanese woman due to an abdominal disorder, associated with a markedly high serum CA19-9 level (2,172.6 U/ml). After endoscopic mucosal resection was performed, the CA19-9 level was drastically decreased and normalized. The scanning view of immunohistochemical staining of CA19-9 exhibited a focal, not diffuse, positive-expression in the hyperplastic epithelium and, especially, in the irregular and fused tubular glands and the mucinous material secreted into the dilated glands. In particular, microscopic examination of the strongly CA19-9-positive areas showed structurally atypical epithelium containing mildly to focal moderately enlarged nuclei and prominent nucleoli with loss of cellular polarity, estimated as adenocarcinoma. No stromal invasion was evident. Immunohistochemically, distinct nuclear stainings for p53 and Ki-67 were seen, occasionally conforming to the CA19-9-positive atypical cells, respectively, confirmed by double immunostaining. These hyperplastic and atypical cells were classified into the pure gastric phenotype by mucin histochemical methods. Based on these features, we finally made a conclusive diagnosis of CA19-9-producing in situ well differentiated adenocarcinoma of gastric type arising in hyperplastic foveolar polyp. We suggest that the markedly high serum CA 19-9 level could be indicative of carcinoma in polyp at the very least. Virtual Slides The virtual slides for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1692254825554310